Association of growth traits with a structural variation downstream of the KCNJ11 gene: a large population-based study in chickens. Issue 3 (3rd May 2020) - Wang, X.; Wei, C.; Zhang, Z.; Liu, D.; Guo, Y.; Sun, G.; Wang, Y.; Li, H.; Tian, Y.; Kang, X.; Han, R.; Li, Z.
ABSTRACT: 1. The potassium voltage-gated channel subfamily J member 11 gene ( KCNJ11 ) is involved in the insulin secretion pathway. Studies have shown that mutation in this gene is associated with muscle weakness. The objective of the present study was to establish the association between KCNJ11 gene polymorphism and chicken growth performance and to analyse its expression pattern. 2. A novel 163-bp insertion/deletion (indel) polymorphism was identified in the region downstream of the KCNJ11 gene in 2330 individuals from ten populations by polymerase chain reaction (PCR). An F2 resource population was used to investigate the genetic effects of the chicken KCNJ11 gene. Association analysis showed that the indel was significantly associated with chicken growth traits and that the phenotypic value of the ins-ins (II) genotype is higher than that of the ins-del (ID) and del-del (DD) genotypes. 3. Gene expression for different genotypes showed that birds carrying the II allele had a higher expression level than the DD genotypes. Analysis of tissue and spatiotemporal expression patterns indicated that the KCNJ11 gene was highly expressed in muscle tissues, with the highest levels in muscle tissue at one week of age, and that a 10% crude protein diet reduced the expression of this gene, average daily gain and muscle fibre diameter. 4. The results suggested that this novel 163-bp indel has the potential to become a new target for marker-assisted selection.